(untitled) (Bangladesh Critical Care Journal, 2015)
Meliodosis, caused by the gram negative saprophyte Burkholderia pseudomallei, is very difficult to diagnose clinically because of varied presentations and lack of awareness. It causes various clinical manifestations like pneumonia, septicaemia, septic shock, septic arthritis, abscesses in different organs etc. The organism can be difficult to identify in laboratories with little experience of B pseudomallei. For effective and timely initiated treatment, clinicians and microbiologists should communicate with each other. Here we report a case of a middle aged diabetic lady who presented with septic arthritis. Burkholderia pseudomallei was isolated from blood and synovial fluid cultures. The unfortunate woman succumbed to death from septic shock before diagnosis. Bangladesh Crit Care J September 2015; 3 (2): 74-76